2007
DOI: 10.1016/j.joen.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Revascularization of Immature Dog Teeth With Apical Periodontitis

Abstract: This study examined the ability of a collagen solution to aid revascularization of necrotic-infected root canals in immature dog teeth. Sixty immature teeth from 6 dogs were infected, disinfected, and randomized into experimental groups: 1: no further treatment; 2: blood in canal; 3: collagen solution in canal, 4: collagen solution + blood, and 5: negative controls (left for natural development). Uncorrected chi-square analysis of radiographic results showed no statistical differences (p >or= 0.05) between exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
283
3
21

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(329 citation statements)
references
References 32 publications
22
283
3
21
Order By: Relevance
“…If pulp and apical papilla are totally lost, then the root canal space may be occupied by cementum, PDL, and bone (35)(36)(37)(38)(39)(40). By tracing the migration of periodontal cells after pulpectomy in immature teeth, Vojinovic and Vojinovic (41) found that periodontal cells migrate into the apical pulp space during the repair process.…”
Section: The Potential Role Of Scap In Replantation and Transplantationmentioning
confidence: 99%
“…If pulp and apical papilla are totally lost, then the root canal space may be occupied by cementum, PDL, and bone (35)(36)(37)(38)(39)(40). By tracing the migration of periodontal cells after pulpectomy in immature teeth, Vojinovic and Vojinovic (41) found that periodontal cells migrate into the apical pulp space during the repair process.…”
Section: The Potential Role Of Scap In Replantation and Transplantationmentioning
confidence: 99%
“…Literature reports have shown promising treatments for these conditions with pulp revascularization and apexification 17 . Revascularization has been studied as an alternative treatment in some cases of incomplete root formation, because it stimulates the thickening and apical closure of immature teeth [18][19] . However, revascularization may present potential clinical and biological complications, such as crown discoloration 20 , development of resistant bacterial strains and allergic reaction to the intracanal medication 21 .…”
Section: Discussionmentioning
confidence: 99%
“…25,26 However, a recent study on dog teeth has shown that the ingrowth of tissue is more likely to originate from the periodontal ligament consisting of cementum, bone, and dentinelike material rather than pulp tissue. 27,28 These authors suggest that there is approximately a 30% chance of pulp tissue re-entering the pulp space. 28 Further histological research on dogs by this group has reported that the canal dentinal walls were thickened by the apposition of cementum-like tissue they termed 'intra-canal cementum'.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al attempted regenerative endodontics with a different protocol. 27 Fourteen teeth were irrigated with 2.5% sodium hypochlorite and 3% hydrogen peroxide and formocresol was used as an inter-appointment medicament rather than tri-antibiotic paste. Over a follow-up period of 0.5 to 3.5 years, radiographic resolution was considered good to excellent in 93% (13 ⁄ 14) of teeth.…”
Section: Discussionmentioning
confidence: 99%